Performance improvement through motor imagery study of the case in artistic gymnastics - Napolitano, S. (Journal of Human Sport & Exercise, 2017)
The motor imagery is a cognitive process of mental simulation of actions in absence of movement. There are two methods to improve skills learning trough motor imagery: in first person and in third person. The biological basis on which the motor imagery theory is founded by mirror neurons. The aim wants to evaluate the effects of motor imagery practice in training, so it verifies the effects on the skills. The method is experimental and it consists of two steps subsequently. To administrate the questionnaire at athletes in order to evaluate the perception of own skill, called round-off flic, and then to compare their perception with the evaluation of Italian federation of artistic gymnastics method. The data will be being compared with those of judge/technician. By the data there is a more effective internal evaluation and also an improvement in the performance on about 80% of the gymnasts that performed the round-off flic. Interpretation of data concerning evaluation of others emerged a lower outside awareness of the skills that is looked. The innovative aspect of this study is the use of hetero-evaluation tool. It is rarely used, but the data show improvements in the performance and ability to evaluate, after using for 5 months of this methodology. Another innovative aspect is the use of motor imagery in the third person. Finally, there`s and improvements learnings for about 80%. So, providing the athletes and trainers could use practice of motor imagery as a possible application for the improvement of the performance.